Hypertensive disorders in pregnancy gestosis score as a predictor of pre-eclampsia - Dhivya, B.; Kailairajan, Revwathy; Sethuraman, Dhivya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pre-eclampsia (PE) significantly contributes to maternal and neonatal morbidity, particularly in low-resource settings. The hypertensive disorders in pregnancy (HDP) gestosis score integrates clinical risk factors to identify women at risk. This study aimed to assess the ability of the HDP gestosis score to predict PE, analyse associated risk factors, and highlight the importance of early risk stratification in primary care. Methods: This analytical/observational prospective study was conducted on 280 patients at SRM Medical College Hospital, Trichy, between June 2024 and March 2025. Baseline data, including demographics, obstetric history, and medical conditions, were collected from records and interviews during the first visit. The HDP scoring system was applied, and all participants were prospectively followed up until delivery. Results: Among 280 mothers, 46 (16.4%) developed PE. Mothers with PE had a significantly higher mean age (29.7±6.1 years) than those without PE (p<0.001). Obesity (p<0.001), age >35 years (p<0.001), ART use (p<0.001), hypothyroidism (p<0.001), and chronic hypertension (HTN) (p<0.001) were significantly associated. A Gestosis score ≥3 was present in 17.5% of mothers, with 71.7% of them developing PE (p<0.001). The score showed a sensitivity of 71.7%, specificity of 93.2%, negative predictive value of 94.4%, positive predictive value of 67.4%, and an accuracy of 89.7%, confirming its value for early risk stratification and PE prediction in primary care. Conclusions: PE was associated with advanced age, obesity, ART use, hypothyroidism, family history, multiple pregnancies, diabetes, and HTN. An HDP Gestosis score ≥3 predicted PE with high specificity and moderate sensitivity, supporting its use in antenatal risk assessment.